Survivin Measurement improves Clinical Prediction of Transition From Arthralgia to RA—Biomarkers to Improve Clinical Sensitivity of Transition From Arthralgia to RA - Erlandsson, Malin C.; Turkkila, Minna; Pullerits, Rille; Bokarewa, Maria I. (Frontiers in Medicine, 2018)
Background: Arthralgia often predates development of rheumatoid arthritis (RA). A set of joint symptoms commonly found in patients during their transition from arthralgia to RA, has been recently proposed. Aim: To combine clinical and serological markers and to improve recognition of imminent rheumatoid arthritis (RA) among patients with arthralgia. Methods: The total of 1,743 first-visit patients attending the rheumatology ward in Gothenburg for joint symptoms were identified during 12 consecutive months. Among those, 63 patients were classified as RA, 73 had undifferentiated arthritis and 180 had unexplained arthralgia. New RA cases, which prospectively developed during 48 months, comprised the preclinical (pre) RA group. The joint symptoms of the first-visit were analyzed aiming to distinguish patients with arthralgia and arthritis, and patients with pre-RA, who later developed the disease. The receiver operating characteristics curves were constructed. In the model, symptoms with the odds ratio >2.0 between the arthralgia and pre-RA were combined with information about RA-specific antibodies, C-reactive protein (CRP), and survivin in serum. Results: The proposed set of clinical symptoms distinguished the arthralgia patients from RA and pre-RA. Presence of survivin in serum showed strong association with clinical joint symptoms in arthralgia. A combination of symptoms in several small joint areas, increasing number of joints with symptoms, and patient's experience of swelling in small hand joints at the first visit identified pre-RA cases with 93% specificity. Grouping those symptoms with information about survivin, RA-specific antibodies, and CRP (or gender) in the final algorithm achieved 91% specificity and 55.2% of positive prediction for transition from arthralgia to RA. Conclusion: Clinical and serological parameters in combination aid recognition of imminent RA among arthralgia patients with appropriate sensitivity.